Evaluation of the Effects of Paclobutrazol and Cultivation Years on Saponins in Ophiopogon japonicus Using UPLC-ELSD - Peng Sun; Juhua Tong; Xianen Li (International Journal of Analytical Chemistry)
Nowadays, there is a growing concern about the quality of herbs used in traditional Chinese medicine. In this study, we evaluated the impacts of paclobutrazol and cultivation period on steroid saponins in Ophiopogon japonicus. A rapid method to simultaneously determine three principle steroid saponins (ophiopogonins B, D, and D′) using ultraperformance liquid chromatography combined with an evaporative light-scattering detector was developed. The contents of three saponins in paclobutrazol-treated and nontreated Sichuan O. japonicus and those in the 2-year and 3-year Zhejiang O. japonicus were analyzed. The results showed that the saponin contents were sharply reduced in paclobutrazol-treated O. japonicus as compared to the control, whereas the concentrations of the three targeted saponins in Zhejiang O. japonicus varied with the increase in cultivation years, reflecting varied effects on saponins. Our study provided chemical evidences for further quality control and agricultural practices of O. japonicus.